Pediatric Neuro-Ophthalmology - Brodsky, Michael C. (Springer New York : Imprint: Springer, 2016)
Pediatric Neuro-Ophthalmology, 3rd edition provides the single authoritative resource on the pathophysiology, diagnostic evaluation, and treatment of neuro-ophthalmologic disorders in children. This book is encyclopedic in scope, incorporating extensive references for each condition, numerous diagrams and pictures, and a detailed analysis of the clinical disorders included in the differential diagnosis of each condition. The third edition builds upon this format to incorporate new discoveries about mechanisms of disease, new diagnostic modalities, advances in treatment in the field of pediatric neuro-ophthalmology, and updated neuroimaging figures.